(untitled) (Comprehensive Journal of Science, 2025)
Small and medium-sized construction firms play a critical role in Libya’s infrastructure devel-opment and economic activity, yet the sector has experienced persistent instability and high failure rates. This study examines the quality of financial disclosure among Libyan construction SMEs and explores its implications for organizational performance readiness. Using a disclosure-index methodology aligned with international accounting standards, annual reports of 45 privately owned construction firms were analyzed. The results reveal moderate and uneven disclosure levels, re-flecting weak reporting discipline and limited transparency. The study argues that deficiencies in financial disclosure are symptomatic of broader weaknesses in internal process standardization, doc-umentation, and control practices. Financial disclosure is therefore positioned as an outcome of organizational maturity and a prerequisite for institutional credibility and sustainable performance in the Libyan construction sector.